The Effect of Flavonoid Consumption on Blood Pressure: A Systematic Review - Wulandari, Citra (HM Publisher, 2022)
Hypertension is a common condition in which the long-term force of blood against artery walls is high enough to cause health problems, such as heart disease eventually. High blood pressure is known as the